1988
DOI: 10.1177/109019818801500404
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Linking Agents in the Diffusion of Health Promotion Programs

Abstract: This article examines the role of state health department dental offices as linking agents in the diffusion of an effective preventive health program, the fluoride mouthrinse program (FMRP) in public schools. The aim of this program is to prevent dental caries by a weekly mouthrinsing by elementary school students. In contrast to the traditional focus of diffusion research on characteristics of the innovation and characteristics of the adopter, this study emphasizes an ecological approach, i.e., the transmitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…In this regard, we believe that understanding the association between awareness of the PBSP and other indicators of active transportation amenities and use is a useful direction for future research. Other factors that might influence awareness are opinion leaders, linking agents (Monahan and Scheirer, 1988;Valente, 2010;Valente and Davis, 1999), health habits and needs (Carlfjord et al, 2010), high communication networking, and social interactions (Badilescu-Buga, 2013). Communication occurring through social interactions appears as key to widespread information (Pescosolido and Rubin, 2000;Scott and Carrington, 2011;Simmel, 1964).…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, we believe that understanding the association between awareness of the PBSP and other indicators of active transportation amenities and use is a useful direction for future research. Other factors that might influence awareness are opinion leaders, linking agents (Monahan and Scheirer, 1988;Valente, 2010;Valente and Davis, 1999), health habits and needs (Carlfjord et al, 2010), high communication networking, and social interactions (Badilescu-Buga, 2013). Communication occurring through social interactions appears as key to widespread information (Pescosolido and Rubin, 2000;Scott and Carrington, 2011;Simmel, 1964).…”
Section: Discussionmentioning
confidence: 97%
“…As specified in Figure 1, these include characteristics of (1) the organizational context in which the curriculum is implemented; (2) the implementation system, including training in the curriculum; (3) implementers of the program or curriculum; and (4) audiences targeted. School context and other organizational characteristics that have been linked to fidelity include school size and climate, 37 teacher morale, organizational support, 7,12,[38][39][40] and parental support, 41 as well as constraints in time and resources. 41,42 With regard to the implementation system, a number of studies and reviews, 12,37,43,44 as well as guides to effective school-based drug prevention curricula, 3,6 strongly emphasize the importance of training for effective implementation.…”
mentioning
confidence: 99%
“…30,32,33 In DIT terms, Sun Safe Schools was an effort by outside change agents to promote policy adoption; such efforts have been successful with schools on other health topics. 3335 Past research suggested that senior school administrators are instrumental in adoption decisions, while mid-level administrators facilitate implementation. 36,37 Hence, district administrators were the primary target of Sun Safe Schools but program staff tried to identify and work with internal champions at any level.…”
Section: Methodsmentioning
confidence: 99%